Inverse Association Between Helicobacter pylori Infection and Unexplained Isolated Terminal Ileitis: A Retrospective Study - Lei Y (Dove Medical Press, 2021)
Yu Lei,* Xiaoyu Liu,* Jingmei Liu, Min Zhang, Yan Zhou, Wei Yan, Dean Tian, Ping Zhang, Ping Han Department of Gastroenterology, Tongji Hospital of Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, Hubei Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ping Zhang; Ping HanDepartment of Gastroenterology, Tongji Hospital of Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, Hubei Province, People’s Republic of ChinaEmail 845917536@qq.com; hanzhouping@163.comBackground: Isolated terminal ileitis (ITI) is a phenomenon often observed during colonoscopy, but in most cases, the specific etiology of ITI is unclear. Helicobacter pylori (H. pylori) infection has been reported to be associated with a wide variety of diseases, especially gastrointestinal diseases. Here, we conducted a retrospective study to explore a potential correlation between H. pylori infection and unexplained ITI (UITI).Materials and Methods: The retrospective study was conducted at Sino-French New City Branch of Tongji Hospital, Wuhan, China, from April 2017 to October 2020. All subjects underwent total colonoscopy, with the endoscope being inserted more than 10cm into the terminal ileum. Subjects also received a 13C-urea breath test (13C-UBT). Data on the age, gender, endoscopic manifestations, and main clinical symptoms of subjects were collected. The presence of H. pylori infection was defined as a positive 13C-UBT result. Logistic regression models were used to analyze the potential correlation between H. pylori infection and UITI.Results: There were 247 subjects (25.1%) in the H. pylori (+) group and 739 subjects (74.9%) in the H. pylori (-) group. The prevalence of UITI in the H. pylori (+) group was significantly lower than that in the H. pylori (-) group (OR = 0.518; 95% CI 0.281– 0.956; P = 0.035), and there was no difference in other clinical features between groups. Stratification analysis results showed that there was an inverse association between H. pylori infection and UITI in subjects with age < 60 (P = 0.046).Conclusion: These data showed that H. pylori infection was negatively correlated with UITI. Additional studies are needed to validate these findings in a larger cohort as well as to explore the underlying mechanisms.Keywords: Helicobacter pylori infection, unexplained isolated terminal ileitis, colonoscopy, 13C-urea breath test